2020
DOI: 10.1186/s12903-019-0996-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of dental services and associated factors among preschool children in China

Abstract: Background: This study sought to evaluate dental utilization among 3-,4-, and 5-year-old children in China and to use Andersen's behavioural model to explore influencing factors, thereby providing a reference for future policy making.Methods: This study is a cross-sectional study. Data of 40,305 children aged 3-5 years were extracted from the Fourth National Oral Health Survey, which was performed from August 2015 to December 2016. Patient data were collected using a questionnaire, which was answered by the ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 27 publications
3
53
1
Order By: Relevance
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
“…The period of dental service use ranged from six months [23,29] to ever visiting a dentist in one's lifetime (in Saudi Arabia [22] and Brazil [24,25]). While all studies examined predisposing characteristics, nine out of the ten studies examined enabling resources [22][23][24][25][26][27][28][29][30], eight out of the ten studies examined need factors [22,[24][25][26][27][28]30,31] and one study examined psychosocial factors [30]. The studies included covered all age groups in childhood/adolescence.…”
Section: Overview Of Included Studies: Children/adolescentsmentioning
confidence: 99%
“…Self-reported caries prevalence during Wuhan lockdown was 60.8% and. over 30% of children suffered toothache, which might be caused by unavailable dental services [ 12 , 13 ]. This showed that dentists need to pay more attention to the treatment of toothache in pre-schoolers when the epidemic were thoroughly controlled in the future.…”
Section: Discussionmentioning
confidence: 99%
“…40 This approach can provide more realistic estimates, given that individuals who do not perceive the effects of their oral conditions may not seek dental and oral health services. 41…”
Section: Discussionmentioning
confidence: 99%